Revitalization of the Cera Labu Sebagsi Tradition as a Cultural Heritage: Efforts to Preserve and Regenerate the Dompu Coast in an Inclusive and Sustainable Manner - Sukarddin Sukarddin; Ilyas Ilyas; Sulaiman Sulaiman; Idhar Idhar; Lili Suryaningsih (Swarnadwipa, 2026)
The purpose of this research is to learn more about the Cera Labu tradition, which has not been held for the past five years. This research is qualitative and uses descriptive analysis as the method. The data source for this study is the Soro community, obtained from informants. Data were obtained through observations and interviews with several sources in the field. The research results revealed that the Cera Labu tradition was not held due to Islamic religious beliefs, as the ritual is considered idolatrous and contrary to Islamic teachings. Furthermore, the government's budget efficiency measures have made holding such events increasingly difficult. Another reason is that some residents douse road users with dirty sewer water during the Cera Labu ritual, potentially causing a foul odor.